Sustaining Transport Business: Analyzing Succession Planning for Family - Owned Transport Enterprises - Nowshahri, Aliya Fareed (Journal of Global Economy, Business and Finance, 2025)
In the context of business, succession involves the transfer of leadership for the purposes of continuing operations. This paper’s primary goal is to address the importance of succession planning in relation to transport business sustainability. It is revealed that, Succession is based on culture and customs, that one is selected from the family members to take over the business regardless of competence and experience which leads to business sustainability failure. Study show the factors of succession includes culture setup, lack of succession planning knowledge and succession crisis. Finally, it is recommended that succession planning must reflect true succession management process.